PERTIMBANGAN HAKIM DALAM MENENTUKAN HAK ASUH ANAK AKIBAT PERCERAIAN AGAMA HINDU DI BALI - Ni Putu Yuliana Kemalasari (Jurnal Aktual Justice, 2019)
The prominent legal issues in balinese law can be classified in two problems, inheritance and purusa ( descendant ), purusa is an inherent status (comonly for male) after marriage. If there is later a divorce, the judge must consider the decision in applying the law that was enforced in deciding the divorce case. Referring to Balinese customary law, when there is a divorce, the child's custody will fall on the purusa / father because the child will become a descendant of the father's family, whereas in the Decision of the Supreme Court of the Republic of Indonesia number: 126K / Pdt. / 2001 dated August 28, 2003 states that "If the father and mother divorce, then the care of the underage child is left to the closest and familiar person to the child, namely the mother". Therefore, the basis for weighing judges in determining custody of children in Hindu religious divorce in Balinese customary law is to combine two legal mechanisms between customary law and national law, where from the aspect of Balinese customary law which adheres to the purusa system, the right is on the purusa party but because the child is still underage, the child is under the mother's care until the child become an adult, and mother can not prevent the child to exercising rights and obligations in the father's family as purusa.